Bioremediation of heavy metals in contaminated water: conventional vs. advanced methods - Sati, Saurav; Sharma, Pradeep Kumar; Naithani, Pratibha; Jha, Pawan Kumar; Panwar, Varij; Behera, Nikhil Ranjan; Karmakar, Rachan; Prashant,; Mittal, Amit (Frontiers in Water, 2026)
Heavy metal (HM) contamination by cadmium (Cd), chromium (Cr), arsenic (As), zinc (Zn), lead (Pb), mercury (Hg), and other toxic elements in the environment poses substantial threat to public health and different ecosystems. Originating from diverse anthropogenic and natural sources, these elements can induce several ecological disturbances and multi-organ toxicity in humans and wildlife. Conventional biological and physicochemical methods for the removal of HMs, though effective in some contexts, often have limitations such as being energy intensive, costly, and generation of secondary waste. As a result, there is growing interest in exploring cleaner, efficient, and more sustainable approaches like bioremediation. Bioremediation is progressively acknowledged as one of the cost effective and sustainable strategy for pollution abatement by employing plants, bacteria, and other microorganisms capable of eliminating, transforming, or immobilizing HMs. This work aims to provide an overview of the conventional and advanced methods for the remediation of HMs, weighing up their benefits and limitations. Various methods for detection of HMs are also reviewed highlighting suitability, sensitivity, cost, portability, and field applicability. Further, we have discussed about the synergistic advantages of combining biological and physicochemical methods over standalone approaches, highlighting the need of hybrid methods like integration of artificial intelligence (AI) and nanotechnology in bioremediation. Overall, this review highlights bioremediation as a pivotal strategy for achieving cleaner ecosystems and sustainability, while underscoring the need for further research to optimize bioremediation technologies for broader real-world environmental management applications.